New Silver Polypyridyl Complexes: Synthesis, Characterization and Biological Activity on Leishmania mexicana - Navarro, Maribel; Cisneros-Fajardo, Efrén J.; Marchan, Edgar (Arzneimittelforschung, 2006)
Leishmania parasites are the causal agents of leishmaniasis that currently threatens 350 million people in 88 different countries, in the absence of an effective drug. In order to continue the development of transition metal complexes with planar ligands that show interactions with DNA and activity against Leishmania parasites, the synthesis of the complexes [Ag(dpq)2]NO3 (1) and [Ag(dppz)2]NO3 (2), which were obtained by the reaction of silver nitrate with dpq and dppz, respectively, in a 1:2 molar ratio is reported. These complexes were characterized by elemental analysis and 1H-NMR, IR, and UV-vis spectroscopies. The most probable structure for these complexes is tetrahedral, with two molecules of ligand coordinated to the silver atom and a nitrate as a counter ion. Affinity studies of DNA vs. bovine albumin were carried out, and a strong interaction of the complexes with DNA was observed. Bioassays were undertaken in vitro on promastigotes of Leishmania (L.) mexicana exposed to the silver complexes for 48 h. At 10 µmol/L complex 2 induced a leishmanicidal effect (LD23), whilst complex 1 reduced the parasites growth rate by 55 % (LD55). These findings suggest that biological activity could be associated with the interaction of the complexes with the parasitic DNA.
Keywords: Antibiotic agents; Leishmania mexicana; Polypyridyl complexes, antileishmanial effects; Silver complexes, antileishmanial effects